2022
DOI: 10.1007/s00405-022-07732-w
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fat-free mass index on the survival of patients with head and neck cancer

Abstract: Purpose To determine whether muscle mass, defined by fat-free mass index (FFMI) measured with bioelectrical impedance analysis (BIA), is predictive of survival of head and neck squamous cell carcinoma (HNSCC) patients. Methods HNSCC patients treated between 2014 and 2018 at the Department for Nutrition of the Institute of Oncology Ljubljana were reviewed. The FFMI values from the pretreatment BIA measurements and pretreatment body mass index (BMI) were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…35 Other studies have also shown that low FFMI is a risk factor for mortality and postoperative complications, both in unselected cohorts of hospitalized patients and in cancer patients. [36][37][38][39] Yilmaz et al, however, did not find any association between FFMI and mortality in patients with hematological malignancies. 40 This study further demonstrated that weight loss, calculated from patient-reported weight at 6 months prior to diagnosis to start of treatment, was associated with treatment response failure but not with survival.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…35 Other studies have also shown that low FFMI is a risk factor for mortality and postoperative complications, both in unselected cohorts of hospitalized patients and in cancer patients. [36][37][38][39] Yilmaz et al, however, did not find any association between FFMI and mortality in patients with hematological malignancies. 40 This study further demonstrated that weight loss, calculated from patient-reported weight at 6 months prior to diagnosis to start of treatment, was associated with treatment response failure but not with survival.…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, a recent retrospective study identified low pretreatment FFMI as a prognostic factor in patients with normal or high BMI who were treated for lung cancer, breast cancer or upper gastrointestinal cancer, using BIA for body mass composition measurements 35 . Other studies have also shown that low FFMI is a risk factor for mortality and postoperative complications, both in unselected cohorts of hospitalized patients and in cancer patients 36–39 . Yilmaz et al, however, did not find any association between FFMI and mortality in patients with hematological malignancies 40 …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, this result demonstrates the importance of preserving lean tissue in the early cancer stages, to maintain a better nutritional status and outcome. In fact, lean tissue is also associated with better treatment response and, consequently, a better prognosis [ 44 , 45 , 46 ]. Moreover, this study suggests that the PEG duration time positively impacts survival time in HNC patients.…”
Section: Discussionmentioning
confidence: 99%